Self-perceived body image and body satisfaction of adolescents - Justino,Maraísa I. C. (2020)
Abstract Objectives: to evaluate self-perceived body image and body satisfaction of adolescents and their associated factors. Methods: across-sectional study carried out with 200 adolescents from a non-govern-mental organization of Campinas-SP. Self-perceived body image was assessed using a scale of silhouettes and body satisfaction by body areas. Association between sociodemographic and anthropometric data and body image and satisfaction were assessed by logistic regres-sion. Results: seventy percent of normal weight boys and 88% of girls wrongly perceived their nutritional status according to the objective standards. The prevalence of body dissatisfac-tion was 76.5%. Twenty-two percent of adolescents reported dissatisfaction with their body shape. Self-perceived body image was associated with nutritional status (OR= 0.25; CI95%=0.09-0.73), abdominal obesity (Waist/Height ratio- WHR) (OR=26.57; CI95%=3.98-177.18), and gender (OR=2.65; CI95%=1.16-6.05). Conclusions: we identified an important distortion and dissatisfaction with body shape. Girls, overweight/obese adolescents and those with abdominal obesity have more chance to this condition. These findings can subsidize actions that deal with the issue of acceptance of self-image, preventing more serious disorders that may directly affect the health of young-sters.